A radon survey in some regions of Turkey - Yarar, Y; Günaydi, T; Kam, E (ELSEVIER SCIENCE BV, 2005)
This paper presents the experimental data of a radon survey conducted in Dikili Geothermal area and Tekirdag city, located in the west and the northwest parts of Turkey. A time-integrating passive method was applied by installing a number of CR-39 nuclear track detectors in dwellings for 3 months. Then, applying chemical etching to the exposed detectors, nuclear track numbers and corresponding indoor radon concentrations were determined. Radon concentrations of the water resources drawn from wells, municipal supplies, village fountains, and spas were also determined by using a liquid scintillation detector. Soil samples were analyzed by using a gammaray spectrometer connected with an HPGe detector and the natural radionuclide concentrations were obtained. Radon concentrations of the soil samples were calculated from the secular equilibrium between (226)Ra-(222)Rn. Risk probabilities of indoor radon inhalation were calculated. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: indoor radon; CR-39; dose; cancer risk; geothermal; Biophysics; Public, Environmental & Occupational Health; Science & Technology - Other Topics